Molecular Dissection of Bacterial Nanowires - Thomas Boesen (American Society for Microbiology, 2013)
ABSTRACT The discovery of bacterial conductive structures, termed nanowires, has intrigued scientists for almost a decade. Nanowires enable bacteria to transfer electrons over micrometer distances to extracellular electron acceptors such as insoluble metal oxides or electrodes. Nanowires are pilus based and in Geobacter sulfurreducens are composed of the type IV pilin subunit PilA. Multiheme c-type cytochromes have been shown to attach to nanowire pili. Two hypotheses have been proposed for electron conduction in nanowires. The first (termed the metal-like conductivity or MLC hypothesis) claims that the pilus itself has the electron-conductive properties and the attached cytochromes mediate transfer to the final electron acceptor, whereas the second hypothesis (termed the superexchange conductivity or SEC hypothesis) suggests that electrons are “hopping” between heme groups in cytochromes closely aligned with the pilus as a scaffold. In their recent article in mBio, Vargas et al. [M. Vargas, N. S. Malvankar, P.-L. Tremblay, C. Leang, J. A. Smith, P. Patel, O. Snoeyenbos-West, K. P. Nevin, and D. R. Lovley, mBio 4(2):e00210-13, 2013] address this ambiguity through an analysis of strain Aro-5, a G. sulfurreducens PilA mutant lacking aromatic residues in the nonconserved portion of PilA. These residues were suspected of involvement in electron transport according to the MLC hypothesis. The G. sulfurreducens mutant had reduced conductive properties, lending important support to the MLC hypothesis. The data also highlight the need for further and more conclusive evidence for one or the other hypothesis.